Вы находитесь на странице: 1из 8
TARGET IIT-JEE ALL INDIA TEST SERIES 12 t h VELOCITY _ ADVANCED TEST - 5

TARGET IIT-JEE

TARGET IIT-JEE ALL INDIA TEST SERIES 12 t h VELOCITY _ ADVANCED TEST - 5 PAPER

ALL INDIA TEST SERIES

12 th VELOCITY _ ADVANCED TEST - 5

PAPER - 2

ANSWER KEY WITH SOLUTION

MATHEMATICS

SECTION - A

1.

C

2.

C

3.

B

4.

C

5.

C

6.

C

7.

A

8.

B

9.

D

10.

C

11.

D

12.

C

13.

B

14.

D

15.

A

16.

C

17.

B

18.

A

19.

D

20.

C

 

PHYSICS

 

SECTION - A

1.

A

2.

D

3.

D

4.

B

5.

C

6.

A

7.

B

8.

C

9.

B

10.

B

11.

B

12.

C

13.

B

14.

B

15.

C

16.

D

17.

B

18.

A

19.

C

20.

C

     

CHEMISTRY SECTION - A

1.

A

2.

D

3.

A

4.

D

5.

A

6.

C

7.

B

8.

C

9.

B

10.

B

11.

A

12.

A

13.

A

14.

D

15.

B

16.

A

17.

A

18.

C

19.

C

20.

A

16. A 17. A 18. C 19. C 20. A 394 - Rajeev Gandhi Nagar Kota,
16. A 17. A 18. C 19. C 20. A 394 - Rajeev Gandhi Nagar Kota,

394 - Rajeev Gandhi Nagar Kota, Ph. No. 93141-87482, 0744-2209671 www. motioniitjee.com , email-info@motioniitjee.com

1
1

SOLUTIONS

MATHEMATICS

SECTION – A Single Correct

1. C a + b + c d

sq.

a 2 + b 2 + c 2 + 2ab + 2bc + 2ca d 2

(a – b) 2 0, (b – c) 2 0, (c – a) 2 0.

Add

from (1) & (2)

a 2 + b 2 + c 2 ab + bc + ca

(1)

(2)

a 2 + b 2 + c 2

2. C

T

r

1

T

r

= 1

3

1

243

1

T

1

=

 

×

T r . T r+1 = 1

9

d 2

3

1

3

3

1

3

r

1

T 1 =

 

1

9

 

 

1

3

 

r

3

3

3

= 1

5 9

=

1

1

81

3

2r

1

5.

The given equation becomes x 2 – 3x + 2 = 0

Hence

= 1,  = 2 2 +  + 2 = 7

C

We have

1

2

S = 5

5

2

+

3

5

3

S

1

=

2

5 5

2 3

5

3

+

5

4

4

5

4

+

4

5

5

5

5

5

+

+

add

——————————————————

6S

1

=

5 5

6S =

1

5

5

1

1

5

1

5

2

+

1

5

3

1

5

4

=

1   5

   

5

6

+

1

5

5

S =

5

36

Ans.

a n =

3

 

1

81

9

r

  =

1

 

1

27

9

r

 

6. C

The value of determinant = 2 + 2 sin 2

r

1

T

r

T

r

=

1

27 ×

3. B

1

1

9

=

×

r

1

7

8

1

9

1

 

1

  

1

27

9

r

27

1

1

9

=

1

6

3

=

1

216

  

7.

A

f 2 (x) f

1 x

1

x

x  1 1

x

x

f 2

1 x

1

x

f(x)

= 64

64

1 x

1

x

……(1)

……(2)

4.

C

We know that 1 =  log 2 2 3  log 3 2
We know that
1
= 
log
2
2 3
 log
3
2
log 3 2 2  2 log 2 = 3 3
log
3
2
2
 2
log
2
= 3
3

log

2 3

 

 

1   log 3  2 
1 
log
3
2

(Using base changing formula)

64x

2

f (x)

2

f(x)

1 x

64

1

x

3

f (x)

64

x

2

1 x

1

x

f(x)

4

 

2

x (1

x)

(1

x)

 

1/3

    2 x (1  x) (1  x)    
    2 x (1  x) (1  x)    

394 - Rajeev Gandhi Nagar Kota, Ph. No. 93141-87482, 0744-2209671 www. motioniitjee.com , email-info@motioniitjee.com

2
2

8. B

I =

2x(x

6f(x))

f(x)

x)(x

(6f(x)

2

f(x))

2

dx

f’

4

5

=

3

16 1  25
16
1 
25

=

35 = – 5

3

I

=

2x(x

6f(x))

(6f(x)

x)(x

2

f(x))

2

dx

4f'   3

5

 f'  

4   5 
4 
5

= |–15 – 5| = | – 20|

f(x)dx

2

(6f(x) x)(x f(x))

2

+

(1)


10. C

user leibrity rule to get again given that

x f'(g(x)) g’(x) = f(g(x))

f(g(x)) = e 2x

Given that

x f(x) = 3(f(x)) 2 + 2

xf’(x) + f(x) = 6 f’(x)f(x)

g'(f(x)) f’(x)

g(f(x))

e

x

2

f(x)



6f(x)

x = f’(x)

2x

dx

+

g(f(x)) =

g(f(4)) = e 16 = e k k = 16

from (1)

I

f '(x)dx

(x

2

f(x))

2

=

= –

(x 2

f(x))

2

2x

f '(x)

(x

2

f(x))

2

dx

Paragraph

11. D

12. C At x = – 5 f ' (x) changes from + ve to – ve and x = 4, f ' (x) change sign for + ve to – ve hence maxima at x = – 5 and 4. f is continuous and f ' (x) is not defined hence x = 2 must be geometrical sharp corner

13. B

14. D

15. A

16.

C 15 to 16

f

f

(0) = 2

(x) = (e x + e x )

cos x – 2x –

x f '(t) dt

x


0

x

0

 t f '(t) dt

 

I

II

9. D

f(x) = cos 1 (4x 3 – 3x)

=

2 

2

 

3

3

3

1

cos

cos

cos

3

1

1

x

x

x


2 1  x
2
1
x

3

2 1  x
2
1
x

3

 2  1  x
2
1
x

f’(x) =

;

;

;

;

;

;

1

2

1

2

1

x

1

x

x

1

2

1

2

 

1

2

1

2

1

1


1

2  

1

2

x

x

x

 

Sol.

(i)

f (x) = (e x + e x ) cos x – 2x

f’  

3

5

=

3

) cos x – 2x  f’   3 5    = 

35

=

4

15

=

4

x f(x) f(0)

t·f(t)

x

0

x

0

f (t) dt

 

x 0  x  0 f (t) dt       
x 0  x  0 f (t) dt       

394 - Rajeev Gandhi Nagar Kota, Ph. No. 93141-87482, 0744-2209671 www. motioniitjee.com , email-info@motioniitjee.com

3
3

f (x) = (e x + e x ) cos x – 2x – x f (x) + 2x

+

x f (x)

x

0

f (t) dt

f (x) = (e x + e x ) cos x –

x

0

f (t) dt

(1)

differentiating equation (1)

f ' (x) + f (x) = cos x (e x – e x ) – (e x + e x )

sin x

(2)

dy

hence dx

+ y = e x (cos x – sin x) – e xx (cos

x + sin x)

(ii) I.F. of DE (1) is

Ans.(i)

e

x

y · e x =

e

2x

(cos x sin x) dx

(cos x sin x) dx

y

· e x = e

2x

(cos x sin x) dx

– (sinx – cosx)+C

Let

I = e

2x

(cos x sin x) dx

= e 2x (A cos x + B sin x)

solvingA = 3/5 and B = – 1/5 and C = 2/5  3 1
solvingA = 3/5
and
B = – 1/5
and
C = 2/5
 3
1
cos x 
sin x 
 y = e x
5
5
– (sin x – cos x)e –x + 5 2 e –xx
Matrix Match Type
17. B
18. A
x
y 3
z  2
:
=
=
(1)
L 1
3
4
1
17. B 18. A x y 3 z  2 : = = (1) L 1

(passing through P and Q)

L 2 :

x 1

1

y 3

=

0

z 1

=

1

(2)

(passing through R and parallel to

v

ˆ

i

ˆ

k

)

distance of P(0, 3, – 2) from L 2

P N

=

ˆ

(t 1)

i

ˆ

6 j

2(t

ˆ

1) k

now

P N

ˆ

6 j

[

ˆ

(t 1)

i

·

V

(t

=

0 

ˆ

1) k

]

·

(

ˆ

i

ˆ

k)

(t + 1)

+ (t + 1) = 0

hence

P N

=

ˆ

6 j

= 0

 t = – 1

P N
P N

=

ˆ

6 j

= 6

Distance between L 1 and L 2

Equation of plane containing L 1 and parallel to L 2

Ax + B(y – 3) + C(z + 2) = 0

where 3A + 4B + C = 0

and

A + 0B + C = 0

A + C = 0

C

= , A = – ,

B = + /2

equation of plane
equation of plane
equation of plane
equation of plane
equation of plane

equation of plane

x +

(y – 3) + (z + 2) = 0

2

2x – y + 3 – 2z – 4 = 0

2x – y – 2z = 1

(1)

now distance of the point (1, – 3, – 1) lying on the line L 2 from the plane (1)

2  3 2 1 d = = 2 Ans. 3 Area of PQR 
2  3 2 1
d =
= 2
Ans.
3
Area of PQR
ˆ
ˆ
ˆ
QR  a  2
i
10 j
0 k
 ˆ
ˆ
ˆ
QP  b  3
i
4 j
 k
 0 k  ˆ ˆ ˆ QP  b  3 i  4 j
 0 k  ˆ ˆ ˆ QP  b  3 i  4 j

394 - Rajeev Gandhi Nagar Kota, Ph. No. 93141-87482, 0744-2209671 www. motioniitjee.com , email-info@motioniitjee.com

4
4

19.

ab 2

ˆ

ˆ

ˆ

i

j

k

1

5

 

0

 

2[

ˆ

i(5)

 

ˆ

j(1)

 

ˆ

k(4

 

15)]

 

=

3

4

1

 

ˆ

ˆ

ˆ

=

2[5

i

j

11 k]

 
 | a   b | = 25 1121 2 = = 3·49 =
| a
 
b |
=
25 1121
2
=
=
3·49
=
7
3

Distance of (0, 0, 0) from PQR

equation of plane PQR is

=

 

ˆ

(r

p)·n

ˆ

 

ˆ

ˆ

ˆ

ˆ

[x

i

(y

3) j

(z

2) k]·[5 i

j

 

11 k]

= 5x – (y – 3) – 11(z + 2) = 0

= 5x – y – 11z – 19 = 0

distance from (0, 0, 0) of the plane

D

19 19 d = = 25   1 121 147 a b c 1
19
19
d =
=
25
 
1
121
147
a b
c
1
c
a
D =
b c = – 2
(a + b + c)
a
b

[ (a – b) 2 + (b – c) 2 + (c – a) 2 ]

(P)

If

a + b + c 0

and a 2 = ab

D = 0

and

a = b = c

Equation represents identical planes

(Q)

D = 0 Equation will have infinite

many solution

 

ax + by = (a + b)z

bx + cy = (b + c)z

(b 2 – ac)y = (b 2 – ac)z

 

y = z

 

 ax + by + cy = 0

 

ax = ay

x = y

x = y = z

(R)

D 0

 

Planes meeting at only one point

(S)

a + b + c = 0

 

a 2 = ab

 

a = b = c = 0

20.

C

(P) sin 420° cos 390°+cos (–660°)sin (–330°)

sin (360° + 60°) cos (360° + 30°)

– cos (720° – 60°) sin (360° – 30°)

sin 60° cos 30° + cos 60° sin 30°

sin (60° + 30°) sin 90° 1

(Q) tan 315° cot (–405°)+cot 495° tan (–585°)

–tan (360° – 45°) cot (360° + 45°)

– cot (540° – 45°) tan (540° + 45°)

tan 45° cot 45° + cot 45° tan 45°

1 + 1 2

(1

tan8 )(1

tan37 )

(R) (1

tan22 )(1

tan23 )

We know that,

tan A

tanB

tan (A + B) = 1

tan A tanB

tan (8° + 37°) = tan 45°

 

tan8



tan37

= 1

1

tan8 tan37

(tan 8° + tan 37°)

= 1 – tan 8° tan 37°

similarly, tan (22° + 23°) = 1

(tan 22° + tan 23°)

= 1 – tan 22° tan 23°

(i)

(ii)

 

(1

tan8 )(1

tan37 )

Now, (1

tan22 )(1

tan23 )

=

=

(S)

 

1

tan8 tan37



(tan8



tan37 )

1

1

tan22 tan23

1



(tan22



tan23 )

1

1

= 1

 
 

sin

2

x

1

0 <

4

< 1 & 0

3

< 3

are always true

 

4

 

4

= 0 and

+

1

3

sin

2

1

3

x

sin

2

x

= 0

= 0

2    1 3 x    sin 2 x = 0 
2    1 3 x    sin 2 x = 0 

394 - Rajeev Gandhi Nagar Kota, Ph. No. 93141-87482, 0744-2209671 www. motioniitjee.com , email-info@motioniitjee.com

5
5

1. A

N x = 2T sin

It is small then,

N x = 2T and N y = dm. g N 2T  x tan
N x = 2T
and N y = dm. g
N
2T 
x
tan  =
N
dm.g
y

tan45º =

2T

dm.g

2T

W.2

=  N dm.g y tan45º = 2T  dm.g  2T  W.2  .2

.2

T =

W

2

.

PHYSICS
PHYSICS

7.

2. D V B cos60º = V A cos60º

V B = V A . 3. D R = mV ,R  ,V 
V B = V A .
3. D
R =
mV ,R
,V
.
qB

4. B

For minima,

x = (2n + 1) 2 0.50 = (2n + 1)

2

1 = (2n + 1) 300

f

f = (2n + 1) × 300

8.

dian

9.

300 Hz, 900 Hz, 1500 Hz, i.e. odd multiple of 300 Hz are missing.

5. C Dispersive power is the property of material.

6. A Frequency received and emitted by wall will be equal

f'

c

v

c

n

frequency received by observer directly = n frequency heard by observer after reflection

c c  v c  v f ''  c f '  
c
c
v
c
v
f ''
c f '
n
n
c
 v
c
v
c
c
v
 v)n
beat heard = (c c
 n
 v
(c
v)n
n(c
v)
2nv
=
c
v
c  v
B
y max
30º
1 sin30º =  sin90º
0.5 = (1.5–y max )
y max = 1m.
C
 = ( – 1)A
1
1
1
=
(1.5 – 1) ×
degree =
360 ra-a-
2
1
y
= f =
6 cm.
B
v
0
r q
B
3
=  4
r
v.r sin 
 qvR
0
0
=
q
3
3/2
4
r
4
2
2
R
x
 1/2
2
2
r 
 R
 x
sin  = R
.

r

x   1/2 2 2 r   R  x sin  = R
x   1/2 2 2 r   R  x sin  = R

394 - Rajeev Gandhi Nagar Kota, Ph. No. 93141-87482, 0744-2209671 www. motioniitjee.com , email-info@motioniitjee.com

6
6

10. B V' = V[1 + T] = A av h [1 + T]

p' =

V'

g

A

av

h 1

  

T

  1

  

T

A'

av

   

1

T

A'

av

g

A' av > A av in case of (B), p B < p i

A' av < A av in case of (A), P A > P i

A' av = A av in case of (C), p c = p i

11.

B

0 = 1 m + 3yd 2D –0.5 t

3 yd

2 D

=–0.5 m

y

=

=

10

 

6

 





1m

3

1

10

3

10

3

1

3

3 mm, below centre.

12. C

 10  D 3000 10   1  2  = = 2×10
 10
 D
3000 10
1
2
=
= 2×10 –4 m=
 3
n d
3
1
10
2
0.2mm.
13. B
600+q
150+q
q
+
200V
600
q
150
q
200– 
=0
 
6
 
 
3
 

17.

18.

B

f B =

2v f

0 0

v

v

s

f A = 0

f c =

2VV

s

v

2

V

s

2

=

2

10

300

6000

=400 Hz

2

350

50

6000

400 300

=1750 Hz

f D = f E = 4f 3 –f = 3 =2000 Hz.

f

A

A

(A) Dispersion is due to different refractive

S; B R; C Q; D P

index for different wavelength.

(B)

Obvious – S

(C)

Beats – small frequency difference – Q

(D)

Refraction is due to speed difference

(E)

Deviation in any ray is due to different

speed in the different medium.

19.

C

A Q,R ; B P ; C Q ; D Q

(a)

leads source voltage because reactance is capacitive

, current

1/

C

R

tan =

 = 4

(b) Pure inductive circuit =

behind source voltage because inductive

, current lags

2

reactance is

(c)

behind source voltage because reactance is

inductive.

= 4 , current lags

L

R

tan =

= 1

1200 – 600 – q - 300 – 2q = 0

20.

C

300 = 3q

A

Q,S ; B P,R ; C P,R ; D Q,S

q

= 100 c

(A)

Due to current carrying wire, the magnetic field

Charge on capacitor P = 600 + 100 =

700c

 

Charge on 3 F capacitor = 250 c

14.

B Charge on capacitor P remains same.

15.

C

Current drawn is maximum at resonant an- gular frequency. L eq = 4 mH C eq = 10 F

=

1

= 5000 rad/sfrequency. L e q = 4 mH C e q = 10  F  =

16. D

C decreases thereby increasing resonant

eq

frequency.

in loop will be inwards w.r.t. the paper. As current is increased, magnetic flux associated with loop in- creases. So a current will be induced so as to de- crease magnetic flux inside the loop. Hence Induced current in the loop will be anticlockwise. The cur- rent in left side of loop shall be downwards and hence repelled by wire. The current in right side of loop is upwards and hence attracted by wire. Since left side of loop is nearer to wire, repulsive force will domi- nate. Hence wire will repel the loop

(B)

Options in (B) will be oppsite of that in (A)

(C)

When the loop is moved away from wire, mag-

netic flux decreases in the loop. Hence the options for this case shall be same as in (B)

(D) When the loop is moved towards the wire, mag-

netic flux increases in the loop. Hence the options

for this case shall be same as in (A)

Hence the options for this case shall be same as in (A) 394 - Rajeev Gandhi
Hence the options for this case shall be same as in (A) 394 - Rajeev Gandhi

394 - Rajeev Gandhi Nagar Kota, Ph. No. 93141-87482, 0744-2209671 www. motioniitjee.com , email-info@motioniitjee.com

7
7

CHEMISTRY

1. A

SECTION - A

(C 2 H 5 ) 3 N + CH 3 COOH salt

G

WB WA Eq. Point Vol. of WB added
WB
WA
Eq. Point
Vol. of WB added

2.

D Largest no. of salve particle’s highest will be B.P.

3. A

4. D

p

p

P S =

B

0

A

0

= 100 n A = 1

= 60 n B = 3

p

0

A

× X A +

p

0

B

× X B

1 3

P S = 100 × 1

= 25 + 45 = 70 given P S = 75 Hence calculated P S is less than given P S So D, all options are correct

3

+ 60 × 1

3

5. A

6. C

B

7.

8. C

9. B

S

C

O

2

2

2

Paramagnetic two unpaired electrons Diamagnetic zero unpaired electrons Paramagnetic two unpaired electrons

10. B Bulky group at equatorial position is more stable

11. A

12. A

13. A

14.

D

15. B

16. A

17. A

A–PQS B–PQRS, C–QR, D–QS

(A) Cl fcc, Na + all OV

OV = 4

tv

= 8

Total voids = 12

4

1

voids occupied =

(B) S fcc, Zn +2 atternate tv

OV = 4

12 3

tv = 8 voids occupied =

4

1

12 3

18.

C

19. C

20. A

(P)H 2 O(s) V < 0

T m

(P)H 2 O(s)  V < 0 T m

H 2 O()

w

> 0

G = 0 S > 0 q p = H > 0

(Q)

CO 2 ()

T m

CO 2 (  ) T m

CO 2 (s)

V < 0

w > 0

G = 0 S < 0 q p = H < 0

(R) T

V < 0

w > 0

S =

q = 0

q rev

T

0

(S)

w > 0

U = a + w

0

+

S = nRln

V

2

V

1

= – vee

> 0  U = a + w 0 – +  S = nRln V
> 0  U = a + w 0 – +  S = nRln V

394 - Rajeev Gandhi Nagar Kota, Ph. No. 93141-87482, 0744-2209671 www. motioniitjee.com , email-info@motioniitjee.com

8
8

Оценить